LITERATURE REVIEW: INDEPENDENCE CHARACTERS IN PHYSICS SUBJECTS - Win, Khin Than; Wulandari, Mashelin (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
The method used is System Literature Review. This method is used with the intention of identifying, evaluating and synthesizing research results and ideas that have been produced by researchers and practitioners. Data collection techniques using literature studies. Sampling data was collected by looking for several scientific articles from the results of previous researchers' research experimentally, descriptively, or developmental research, based on literature studies, to be studied further and conclusions drawn from the research topics studied. The article review process in this study discusses the scope of evaluation of high school students' spectacle learning. The instruments used in data collection included a review of scientific articles sourced from the last 25 references from Google Scholar, hands-on science, and article research gates reviewed by researchers who focused on the topic. researched. Then data analysis was carried out in this study using a synthetic matrix.